An online survey study of the association between tinnitus and hyperacusis using validated questionnaires. (1st August 2022) - Husain, Fatima T.; Chappell, Jenise; Tai, Yihsin
Abstract: Objective: To investigate the association between the highly comorbid tinnitus and hyperacusis conditions using standard questionnaires. Design: A cross-sectional internet-based survey consisted of general demographic questions, questions about hearing and emotional status, Tinnitus Primary Function Questionnaire (TPFQ), and Hyperacusis Questionnaire (HQ). Study sample: Six hundred sixteen completed surveys were obtained primarily from students and staff in a large university. Results: About 6% of the respondents could be classified as having hyperacusis based on the criterion of HQ scores ≥ 28 and had significantly increased odds of reporting having tinnitus (OR 10.11; 95% CI 3.76–35.3). Tinnitus severity (TPFQ) and HQ scores were correlated regardless of the hearing loss status. When predicting TPFQ scores, after controlling for demographic factors and affective states, hyperacusis status became an insignificant predictor. In contrast, both affirmative answers to having anxiety and depression, together with hearing loss status and tinnitus were significant predictors of HQ scores. Conclusions: Having hyperacusis did not appear to contribute significantly to tinnitus severity, but having tinnitus contributed to the likelihood of having hyperacusis. Our findings provide a nuanced view of how tinnitus and hyperacusis conditions co-occur and influence each other, which may be valuable to clinicians and researchers.